Analisis Penerapan Sistem Politik Rasulullah serta Relevansinya di Indonesia sebagai Negara Modern (Studi Pemerintahan di Kecamatan Anyer, Provinsi Banten) - Saipul Nasution; Muhammad Azrul Amirullah; Lu’lu Galih Martajaya (AHKAM, 2025)
This study is grounded in the evolving political, legal, and social dynamics in Indonesia, where, despite not being a religious state, Islam as the majority religion continues to exert a significant influence on the direction of change. The study aims to provide an in-depth analysis of the implementation of the Islamic political system and to evaluate its relevance in the context of Indonesia as a modern state based on Pancasila, with a particular focus on governmental practice in Kecamatan Anyer, Banten Province. A qualitative method with a phenomenological approach was employed, concentrating the analysis on the administration of sub-district government. The findings show that the integration of the Islamic political system in Indonesia is not realized through the formalization of an Islamic state ideology, but rather through the adaptation and negotiation of Islamic values within a democratic and pluralistic framework. In the context of the Anyer Sub-District Government, the relevance of Islamic political values is evident in their function as a source of ethics and morality that contributes to shaping the character of public officials and to formulating just and civilized policies. The apparatus of Kecamatan Anyer have applied values consistent with the Prophet’s political principles, although implementation remains uneven due to bureaucratic constraints and low levels of community participation. The values of syura (consultation), justice, and exemplary leadership are shown to be relevant in supporting the effectiveness of development deliberations and in improving the quality of public service. This study affirms that the Prophet’s political values can be adapted within a modern democratic system without altering the fundamental structure of the state and can make both theoretical and practical contributions to strengthening governance grounded in ethics and religious values. Overall, the integration of the Prophet’s political values can serve as an applicative guideline for improving the quality of local government in Indonesia.